Geokemične lastnosti tal, poplavnega sedimenta ter stanovanjskega in podstrešnega prahu na območju Mežice - Šajn, Robert (Geologija, 2000)
Spatial distributions of geochemical associations were distinguished based on the chemical analyses of samples. Natural geochemical distributions of elements were distinguished from anthropogenic ones. Twenty chemical elements were considered (Al, Ca, Fe, K, Mg, Si, Ti, Ba, Co, Cr, Cu, Mn, Mo, Ni, Pb, Rb, Sr, V, Zn and Zr). Three natural geochemical associations (Si-Al-K-Rb-Ni-Cr-Co-Ba-Sr, Ti-V-Fe-Zr-Mn-Co, Ca-Mg-Mo-Cu-Ba) and an anthropogenic association Pb-Zn were determined. The anthropogenic associationis a result of mining and smelting activity in this area.
Keywords: geokemija; kemična analiza; kovine; Mežica; onesnaženost; pollution; sedimenti; Slovenia; Slovenija; težke kovine